Ciri Estetik Humor Lakon Wahyu Makutharama Sajian Ki Suyati Purwo Carito - Qohhar Dwi Hatmono; Bagong Pujiono (Institut Seni Indonesia Surakarta, 2021)
One of the puppeteers who has an interesting sense of humor is Ki Suyati Purwo Carito in the wayang kulit purwa lakon Wahyu Makutharama. This article is to answer the problem of how the aesthetic form of humor in Ki Suyati Purwo Carito pakeliran. The method used include observation, literature study and interviews. The approach used is by looking at the humor from various techniques, such as riddle, ridicule, cunundurum, and others. The results obtained show that Ki Suyati’s specific humor shows his characteristic personality in presenting pakeliran. The humorous and vulgar dialogue but not striking, give the impression and message to the audience to always think intelligently without leaving the expectations of human imagination with his point of view.